The Projector : a rediscovered masterwork - Vaughn-James, Martin, 1943-2009 (New York Review comics., 2022)
Linked graphic novels that guide the reader (and a bespectacled Everyman) through landscapes built out of both the everyday and the nightmarish. Jam-packed superhighways, plummeting horses, vast urban wastelands, colossal businessmen, demented cartoon animals, and interstellar oranges are just a small part of Vaughn-James's prophetic vision of society's turn away from the natural world to the artificial.